Mesenchymal Stromal Cells Suppress Hippocampal Neuron Autophagy Stress Induced by Hypoxic-Ischemic Brain Damage: The Possible Role of Endogenous IL-6 Secretion - Miao Yang; Wuqing Sun; Lu Xiao; Mulan He; Yan Gu; Ting Yang; Jie Chen; Xiaohua Liang (Neural Plasticity)
Background. Increasing evidence has revealed that mesenchymal stromal cell (MSC) transplantation alleviates hypoxic-ischemic brain damage (HIBD) induced neurological impairments via immunomodulating astrocyte antiapoptosis effects. However, it remains unclear whether MSCs regulate neuron autophagy following HIBD. Results. In the present study, MSC transplantation effectively ameliorated learning-memory function and suppressed stress-induced hippocampal neuron autophagy in HIBD rats. Moreover, the suppressive effects of MSCs on autophagy were significantly weakened following endogenous IL-6 silencing in MSCs. Suppressing IL-6 expression also significantly increased p-AMPK protein expression and decreased p-mTOR protein expression in injured hippocampal neurons. Conclusion. Endogenous IL-6 in MSCs may reduce autophagy in hippocampal neurons partly through the AMPK/mTOR pathway.